Analisis Fenomena Phubbing pada Pola Komunikasi Mahasiswa Generasi Z di Universitas Muhammadiyah Buton - Zafarudin, Zafarudin; Hastuti, Hastuti; Putra, M.Rizal Ardiansah (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the impact of the Phubbing phenomenon on the communication patterns of Generation Z students at Universitas Muhammadiyah Buton. Using a descriptive qualitative approach, this research reveals that Smartphone dependence, job demands, peer influence, introverted personality traits, and personal issues are the main factors driving Phubbing behavior. Phubbing has been shown to reduce the quality of face-to-face communication and affect students' social interactions and academic performance. In conclusion, Phubbing significantly impacts students' communication patterns, highlighting the need for a balance between technology use and direct interaction.